Comparison of Anthropometric Measurements in Premature Neonates Receiving High-Dose vs Low-Dose Parenteral Amino Acid (PAA) Nutrition: A Randomized Controlled Trial - Akhtar, Ayesha; Imtiaz, Verda; Aziz, Musfirah; Farooq, Hafsa; Shahid, Shehriyar; Iqbal, Bushra; Iqbal, Bushra (Biological and Clinical Sciences Research Journal, 2025)
: Extra-uterine growth retardation in preterm neonates is associated with poor short and long-term outcomes. Adequate early parenteral nutrition, particularly amino acid supplementation, is essential to support optimal growth and development. Objective: To compare mean changes in anthropometric measurements among preterm neonates receiving high-dose versus low-dose parenteral amino acid nutrition. Methods: This randomized controlled trial was conducted at the Department of Pediatrics, Holy Family Hospital, Rawalpindi, from May to November 2023. A total of 270 preterm neonates born at less than 37 weeks of gestation were enrolled and randomly allocated into two equal groups of 135 each. Group A received high-dose parenteral amino acids starting at 2 g/kg/day from the second day of life with increments of 0.5 g/kg every 24 hours up to a maximum of 3.5 g/kg/day. In comparison, Group B received low-dose parenteral amino acids, starting at 1 g/kg/day with similar daily increments up to a maximum of 2 g/kg/day. Amino acid infusion was initiated 24 hours after birth. Anthropometric parameters, including weight, length, and head circumference, were recorded at baseline, day 7, day 14, and day 21 of life. Data were collected using a structured proforma and analyzed using SPSS. Results: At 21 days of life, preterm neonates receiving high-dose parenteral amino acids demonstrated significantly better anthropometric outcomes compared to the low-dose group. Mean weight was 1301.15 ± 28.48 g in the high dose group versus 1245.53 ± 17.02 g in the low dose group (p = 0.0001). Mean length was 37.80 ± 0.28 cm compared to 37.39 ± 0.13 cm (p = 0.0001), and mean head circumference was 28.99 ± 0.40 cm versus 27.58 ± 0.16 cm, respectively (p = 0.0001). Conclusion: High-dose parenteral amino acid nutrition is associated with significantly improved weight gain, linear growth, and head circumference in preterm neonates compared to low-dose regimens, supporting its role in optimizing early postnatal development.